Quelles interactions entre le travail, la vie personnelle et le handicap? Étude de la portée sur les expériences de conciliation travail-vie personnelle des personnes travailleuses ayant des incapacités motrices ou des maladies chroniques - Francis Charrier; Normand Boucher; Bernadette Dallaire (Perspectives Interdisciplinaires sur le Travail et la Santé)
Work-life balance is a key public and scientific concern today. However, little attention has been given to the realities of disability in this area. This article presents the findings of a scoping study on the work-life balance experiences of workers with motor disabilities or chronic illnesses. It highlights how studies have conceptualized their work-life interface, the realities that may influence their work-life balance, the main environmental and personal factors supporting or hindering its achievement, as well as the adaptive strategies employed to sustain it. Theorizing the work-life interface of workers with motor disabilities or chronic illnesses requires acknowledging the impact of: 1) their socially disadvantaged positions, 2) the barriers and resources they encounter, 3) the invisible work performed across their life domains, and 4) ableist discourses contributing to the physical, psychological, and temporal pressures they face daily.